Optimization of grooved micromixer for microengineering technologies - Sabotin, Izidor (Informacije MIDEM, 2013)
Due to the absence of turbulent flow and the slow diffusion process, mixing of solutions at micro-scale is a difficult task. This paper describes the optimization route towards the efficient design of a bottom grooved micromixer. Based on thoroughly discussed mixing mechanisms, the optimization was performed using FEM numerical simulations and the starting geometry was a Staggered Herringbone Mixer (SHM) groove design. Optimization procedure consists of two sequences: (I) one SHM groove geometry is optimized based on the magnitude of transversal velocity at the end of the groove and (II) different configurations of six grooves are investigated taking into account capabilities and limitations of microengineering technologies (MET ). Newly developed designs were benchmarked against the established SHM design and a better efficiency was achieved. Additionally, a good mixing efficiency was also achieved with a modified Slanted Groove Micromixer (SGM). A SGM prototype was machined by micro electrical discharge milling (EDM) technology. The simulation results were experimentally verified with flow visualization and a good agreement was observed. Due to simple 2.5D geometry and efficient mixing properties the proposed micromixer design is adequate to be used in the Lab-On- A-Chip (LOC) systems.
Keywords: microengineering; mikroinženirstvo; mikromešalniki; micromixers; microstructures; mikrostrukture; mikroobdelava; micromachining; optimizacija; optimization; EDM; elektroerozija; micro electrical discharge milling; mikro elektroerozijsko dolbenje; microfluidics; finite element method; metoda končnih elementov; design optimization; simulacije; FEM